Patient Satisfaction with Fentanyl Sublingual Spray in Opioid‐Tolerant Patients with Breakthrough Cancer Pain. Issue 6 (25th July 2014) - Rauck, Richard; Parikh, Neha; Dillaha, Larry; Barker, Jerry; Stearns, Lisa
Abstract Objectives Breakthrough cancer pain (BTCP) is associated with decreased satisfaction with around‐the‐clock opioid therapy. This analysis examined patient satisfaction with fentanyl sublingual spray for BTCP during the open‐label titration period of a randomized, placebo‐controlled study. Methods Opioid‐tolerant patients with 1 to 4 daily BTCP episodes were included. During a 26‐day, open‐label titration phase, a successful dose (100 to 1600 mcg) of fentanyl sublingual spray was established that provided effective analgesia for 2 consecutive BTCP episodes with tolerable side effects. The Treatment Satisfaction Questionnaire for Medication (TSQM) was administered at baseline to assess satisfaction with previous BTCP medication and at the end of the titration to assess satisfaction with fentanyl sublingual spray. Results Of 130 enrolled patients, 115 (88.5%) had a TSQM measure at baseline and at the end of their titration period. Scores on all 4 TSQM domains increased from baseline to end of the titration, with mean (standard error [SE]) improvements of 22.3 (2.3) for effectiveness, 7.7 (3.2) for side effects, 6.8 (2.2) for convenience, and 12.9 (2.8) for global satisfaction (P < 0.05 for all). Satisfaction with symptom relief (26.1% to 77.4%) and onset of action (21.7% to 82.6%) also improved from baseline to end of titration. At least one adverse event (AE) was reported by 78 patients (60.0%). The most common AEs considered possibly or probably related to study medication were dizziness, somnolence, and nausea (n = 10 [7.7%] each). Discussion These data indicate markedly improved satisfaction among patients receiving fentanyl sublingual spray relative to previous BTCP medications.